Synthesis, characterization, and applications of iron oxide nanoparticles - Abrar Hussain; Yasar, Muhammad; Gulzar Ahmad; Muhammad Ijaz; Aziz, Abdul; Gharib Nawaz, Muhammad; Ahmad Khan, Faraz; Iqbal, Hamza; Muhammad Nadeem; Ahmad, Dawood; Farida Anjum; Sulaiman Faisal; et al. (International Journal of Health Sciences, 2023)
Objective: The green synthesis method for nanoparticles is getting more attention globally, due to its lesser cost, non-hazardous, and eco-friendly nature. The novelty of the present work is to investigate the anti-bacterial and degradation activity of the green synthesized Iron Oxide NPs. Methods: In this study, the Iron Oxide NPs were synthesized through a green synthesis route from leaves of Ficus Palmata. UV-Vis confirmed Iron Oxide NP’s peaks between (230–290 nm), while Fourier transforms infrared spectroscopy analysis showed that several groups were involved in reduction and stabilization. Results: Results indicated that the highest photo thermal activity was shown in light and it was almost 4 folds greater than the control. Similarly, Iron Oxide NPs showed excellent antimicrobial potential against bacterial species “Salmonella typhi” “Xanthomonas Oryzae” and “Lactobacillus” at low concentrations (150 μg/mL). Hemolytic assay results showed that the toxicity was lesser than 5% at both dark and light conditions. Moreover, we also evaluated the photo-catalytic potential of Iron Oxide NPs against methylene orange. Results indicated that almost complete degradation was noted after 90 min in the presence of continuous light. All tests were performed in triplicates. All the data was subjected to P-test (P < 0.5) using Excel and graph pad (V.5.0). Conclusion: Iron Oxide NPs holds a promising future and could be used in treating diseases, and microbial pathogenesis and also could be used as a vector in drug delivery. Moreover, they can also eradicate persistent dyes and could be used as an alternative to remediate pollutants from the environment.